2020
DOI: 10.1002/adfm.202002633
|View full text |Cite
|
Sign up to set email alerts
|

A One‐Pot Route to Faceted FePt‐Fe3O4 Dumbbells: Probing Morphology–Catalytic Activity Effects in O2 Reduction Catalysis

Abstract: The design and synthesis of faceted nanoparticles with a controlled composition is of enormous importance to modern catalyst engineering. Faceted FePt‐Fe3O4 dumbbell nanoparticles are prepared by a simple, one‐pot technique that avoids the need for expensive additives or preformed seeds. The faceted product consists of an FePt octopod and a cubic Fe3O4 lobe, of mean diameter 13.6 and 14.9 nm, respectively. The mass normalized activity for electrocatalytic oxygen reduction shows that this new structure types ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…7,8 In particular, numerous works have reported the synthesis of noble metal nanoparticles (NPs), wires, rods and tubes. 9,10 These have been targeted for their remarkable physical and chemical features and have demonstrated applications in sensing, catalysis, biomedicine, therapy, and optical devices. Noble metal NPs (such as Au, Ag, Pd, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…7,8 In particular, numerous works have reported the synthesis of noble metal nanoparticles (NPs), wires, rods and tubes. 9,10 These have been targeted for their remarkable physical and chemical features and have demonstrated applications in sensing, catalysis, biomedicine, therapy, and optical devices. Noble metal NPs (such as Au, Ag, Pd, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…[10,71,72] This intense research interest is owed to their superior properties, often observed specifically for anisotropic structures. [1,6,10,[62][63][64][65][73][74][75][76] Again, NP characterization to understand structure-activity relationships within these complex systems is a significant challenge.…”
Section: Edxs Tomographymentioning
confidence: 99%
“…
wide range of social and economic challenges. [1][2][3] Increasingly complex materials can be prepared for optimized application performance from a wealth of synthetic techniques, including surfactant-, seed-, and additive-mediated procedures, [4][5][6][7][8] which has directly challenged materials characterization to bridge the knowledge gap between synthesis and application performance. [3,[9][10][11] The crystallinity, surface faceting, morphology, as well as elemental distribution and oxidation state, have a profound influence upon nanomaterials properties; all of which can be understood by means of transmission electron microscopy (TEM).Electron tomography (ET) has become an indispensable technique for the 3D characterization of nanoparticles during the last decade.
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the incorporation of a transition metal can be a route to reducing the cost and increasing the catalytic performance [8,9]. Wheatley et al reported that bi-metallic alloy (FePt) nanoparticles comprising transition metal oxide (Fe 3 O 4 ) showed great oxygen reduction capability because of the donation of electron density from Fe 3 O 4 to Pt [10]. FePt-Fe 3 O 4 nanoparticles were synthesized using an organic solvent at a relatively high temperature (<200 • C) under argon atmosphere.…”
Section: Introductionmentioning
confidence: 99%